Societal Costs of Rheumatoid Arthritis in China: A Hospital‐Based Cross‐Sectional Study. Issue 4 (April 2014) - Xu, Chuanhui; Wang, Xiuru; Mu, Rong; Yang, Li; Zhang, Ye; Han, Shuling; Li, Xiaofeng; Wang, Yongfu; Wang, Guochun; Zhu, Ping; Jin, Hongtao; Sun, Lin; et al.
<x xml:space="preserve">Abstract</x> Objective To estimate the annual direct and indirect costs of rheumatoid arthritis (RA) in China and identify the predictors for cost of illness. Methods A cross‐sectional study of cost of illness from the societal perspective was conducted on 829 patients with RA in 21 tertiary care hospitals in China between July 2009 and December 2010. Data on demographics, clinical variables, and components of costs were collected by physician interview. Costs were represented in 2009 US dollars using purchasing power parity estimates. Univariate and multivariate linear regression analyses were performed to identify the predictors for cost of illness. Results The mean ± SD total cost of RA in China was $3, 826 ± $5, 659 per patient‐year, given a gross domestic product per capita of $6, 798 in China in 2009. Direct costs and indirect costs comprised 90.0% and 10.0% of the total costs, respectively. Drug expense represented approximately half of the total costs, dominated by biologic agents (48.2%) and disease‐modifying antirheumatic drugs (23.5%). Additionally, the cost of extracted herbal drugs and traditional Chinese medicine comprised ∼17.6% of the drug expense. Higher education level, noninsured status, longer disease duration, more extraarticular manifestations, and higher Health Assessment Questionnaire score independently predicted higher total costs. Conclusion Our results provide the first study of costs of RA in China. This study not only demonstrates the economic burden of RA, but also identifies the predictors that could be interventional factors to reduce the societal costs of RA in China.